2014
DOI: 10.1128/iai.01876-14
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Burkholderia cepacia Complex Bacteria in Cystic Fibrosis Lungs and Interactions with Pseudomonas aeruginosa in Hypoxic Mucus

Abstract: eThe localization of Burkholderia cepacia complex (Bcc) bacteria in cystic fibrosis (CF) lungs, alone or during coinfection with Pseudomonas aeruginosa, is poorly understood. We performed immunohistochemistry for Bcc and P. aeruginosa bacteria on 21 coinfected or singly infected CF lungs obtained at transplantation or autopsy. Parallel in vitro experiments examined the growth of two Bcc species, Burkholderia cenocepacia and Burkholderia multivorans, in environments similar to those occupied by P. aeruginosa in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
110
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 74 publications
6
110
2
Order By: Relevance
“…Previous studies have demonstrated that a well-studied CF pathogen, P. aeruginosa, colonizes the respiratory tract of CF patients and triggers an immune response (34)(35)(36)(37)(38)(39). It was previously thought to primarily be an extracellular pathogen, which is supported in a histological study of CF lungs (33), though other work in eye models suggests that P. aeruginosa may be able to invade and survive inside host cells (40)(41)(42)(43)(44). Both B. cenocepacia, the best-studied of the BCC members, and P. aeruginosa have been shown to induce production of cytokines (i.e., tumor necrosis factor [TNF], interleukin-6 [IL-6], IL-8, and IL-1␀) in murine alveolar macrophages in vitro (45)(46)(47).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have demonstrated that a well-studied CF pathogen, P. aeruginosa, colonizes the respiratory tract of CF patients and triggers an immune response (34)(35)(36)(37)(38)(39). It was previously thought to primarily be an extracellular pathogen, which is supported in a histological study of CF lungs (33), though other work in eye models suggests that P. aeruginosa may be able to invade and survive inside host cells (40)(41)(42)(43)(44). Both B. cenocepacia, the best-studied of the BCC members, and P. aeruginosa have been shown to induce production of cytokines (i.e., tumor necrosis factor [TNF], interleukin-6 [IL-6], IL-8, and IL-1␀) in murine alveolar macrophages in vitro (45)(46)(47).…”
supporting
confidence: 60%
“…More recent work in transplanted or autopsied CF lungs suggests that BCC strains, including B. dolosa and B. cenocepacia, can be found primarily associated within host cells, particularly macrophages, or in mucus (33). Previous studies have demonstrated that a well-studied CF pathogen, P. aeruginosa, colonizes the respiratory tract of CF patients and triggers an immune response (34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…These mechanisms include efflux pumps, chromosomally encoded ␀-lactamases, and decreased outer membrane permeability (5). In addition, B. cepacia complex species are known to grow in the CF lung as a biofilm or in clusters of bacteria (6), which can act as a significant barrier to the effective delivery of drug intracellularly.…”
mentioning
confidence: 99%
“…In fact, all mucosal sites throughout the human body harbor both commensal and pathogenic organisms that possess mucin-degrading enzymes capable of deriving nutrients from host (22)(23)(24). Indeed, several studies have described the degradation and utilization of mucins by CF-associated microbiota (25)(26)(27)(28)(29). For example, multiple studies have shown that P. aeruginosa and other pathogens (e.g., Burkholderia cepacia complex [BCC]) harbor mucin sulfatase activity capable of utilizing sialylated mucin oligosaccharides as a source of sulfur (26,28).…”
mentioning
confidence: 99%